Geneticeskie faktory formirovanija myšecnoj sily i massy u sportsmeno - Aksenov, M. O. (Vestnik sportivnoj nauki; Sports science bulletin, 2019)
Studies are conducted on the basis of the Research Laboratory of Sports Genetics of the Buryat State University. To date, we have conducted research on the search for genetic susceptibility to the manifestation of human power abilities in sports activities on four gene polymorphisms, these are: ACE (angiotensin-converting enzyme), ACTN3 (alpha-actinin 3), PPARGC1A (peroxisome proliferation coactivator) and MSTN (myostatin). As part of this project, the spectrum of the studied polymorphismsof genes was significantly expanded from 4 to 73. Of the 73 polymorphisms studied, 22 were found to be associated with the manifestation of human skeletal muscle strength. Based on our data, it was found that 3 polymorphisms have the greatest genetic contribution, these are two mutations of the Myostatin gene (rs11333758, rs1805086) and polymorphism of the IGF-1 gene (rs35767). At the first stage of work, we studied 178 subjects, at the second stage - 161. In the course of the research, we compared the power indicators of the subjects by the genotypes of each of the studied genes, for example, the group with the LL MSTN genotype was compared with the group of subjects with the KK MSTN genotype, as well as with the heterozygote group. The total number of subjects of the experimental group was 339 people. DNA was collected and analyzed from the buccal epithelium of the oral cavity of athletes with a level of sports qualification not lower than the Master of Sports of Russia. Genotyping was carried out at the Laboratory of Pharmacogenomics of the ICBFM SB RAS and at the Center for DNA Research, LLC at the Institute of Biophysics of the RAS. Using the methods of mathematical statistics, the frequency of occurrence of genotypes in a sample of subjects was established, as well as the relationship of genotypes with the level of development of the power abilities of the subjects.